2005
DOI: 10.1071/bt04011
|View full text |Cite
|
Sign up to set email alerts
|

Preferential outcrossing in Banksia ilicifolia (Proteaceae)

Abstract: The breeding system of Banksia ilicifolia was assessed by performing controlled hand-pollination manipulations on flowers in a natural population in Perth, Western Australia. The percentage of 2000 flowers per treatment converted to fruits and seeds was assessed across 24 recipient plants following (1) self-pollination, (2) local outcross pollination (same population), (3) non-local outcross pollination (pollen sourced from another population 30 km away), (4) unpollinated but bagged flowers and (5) unpollinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Thus, even though B. marginata is self‐compatible, selfed seedlings suffer from inbreeding depression and were 62% less fit than open‐pollinated progeny. A similar result was reported by Heliyanto et al . (2005) for Banksia ilicifolia R.Br.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, even though B. marginata is self‐compatible, selfed seedlings suffer from inbreeding depression and were 62% less fit than open‐pollinated progeny. A similar result was reported by Heliyanto et al . (2005) for Banksia ilicifolia R.Br.…”
Section: Discussionsupporting
confidence: 92%
“…Seed production by banksias relies on pollinators (insects, mammals and, especially, highly mobile birds), and in their absence seed set can be rare or even nonexistent (Whelan & Burbidge 1980; Whelan & Goldingay 1986; Collins & Rebello 1987; Lamont et al 2007; Phillips et al 2010). As a consequence, Banksia in general displays the highest outcrossing rates seen among plants (Scott, 1980; Carthew et al 1996; Heliyanto et al 2005; Coates et al 2007; Lamont et al 2007; Krauss et al 2009), and it is vital therefore that pollinator services are established for viable restored Banksia populations.…”
Section: Discussionmentioning
confidence: 99%
“…Coates et al 2007). Within Grevillea, Banksia and Eucalyptus there is considerable interspecific variation in mating system with species varying from complete selfing to complete outcrossing (Ramsey & Vaughton 1991;Ellis & Sedgeley 1992;Day et al 1997;Kennington & James 1997;Hermanutz et al 1998;Heliyanto et al 2005). Studies of wild populations have shown that bird-pollinated plants in several genera tend to be primarily outcrossing (Hopper & Moran 1981;Day et al 1997;Coates et al 2007).…”
Section: Pollination Strategies (A)mentioning
confidence: 99%